Regulation and financial services development in the ECCB area. - FERACHO, Jackie (1997)
Points out that as major traditional export commodities come under increasing pressure in international markets and official development assistance begins to dry up, many of the OECS countries are becoming increasingly convinced that the development of financial services has a pivotal role to play in the development of their economies. Identifies issues to be resolved if the groundwork for a successful offshore financial services industry is to be laid.